PENDAMPINGAN ADMINISTRASI MELALUI MANAJEMEN PERPUSTAKAAN DAN SARANA PRASARANA DI SMA NEGERI 1 DRAMAGA - Sarifudin; Ade Wahidin; Ujang Andi Yusuf; Rahman; Muhammad Mukhlis (LPPM STAI Muhammadiyah Probolinggo, 2026)
Efficient and effective administrative management is an important aspect in supporting educational activities in schools. One aspect that is often overlooked is library management and infrastructure, which play a major role in creating a conducive learning environment. Therefore, this community service aims to provide administrative assistance at SMA Negeri 1 Dramaga, focusing on library management, administration, and infrastructure. The problems faced by SMA Negeri 1 Dramaga are challenges in administrative management, particularly in library management and infrastructure, which have not been optimized. This has resulted in a lack of efficiency and effectiveness in supporting learning activities at the school. The method used in this community service activity was assistance in the form of direct support in administrative and management services at the school to make them more effective, particularly in library management and infrastructure. This activity was carried out in collaboration with school staff, particularly administrative staff, librarians, and the infrastructure department. The results of this community service program have succeeded in improving administrative services at SMA Negeri 1 Dramaga, particularly in library management and infrastructure. Librarians and school administrative staff are now able to implement more structured and efficient management. Additionally, evaluations show significant improvements in administrative management, which have a positive impact on learning activities at the school.